Concepts in Middle Kingdom funerary culture: proceedings of the Lady Wallis Budge anniversary symposium held at Christ's College, Cambridge, 22 January 2016 - Nyord, Rune (Culture and history of the ancient Near East, 2019)
Intro -- ‎Contents -- ‎Preface -- ‎Figures and Tables -- ‎Chapter 1. Introduction: Egyptian and Egyptological Concepts (Nyord) -- ‎Chapter 2. Projection of Self in Middle Kingdom Tombs and Coffins (Bickel) -- ‎Chapter 3. The Concept of 'Letters to the Dead' and Egyptian Funerary Culture (Donnat) -- ‎Chapter 4. How 'Royal' (and 'Mythical') Are the Coffin Texts? Reflections on the Definition and Function of Some Etic Concepts in a Middle Kingdom Funerary Text Corpus (Goebs) -- ‎Chapter 5. How 'Funerary' Are the Coffin Texts? (von Lieven) -- ‎Chapter 6. Burial Demography in the Late Middle Kingdom: a Social Perspective (Miniaci) -- ‎Chapter 7. The Concept of ka between Egyptian and Egyptological Frameworks (Nyord) -- ‎Chapter 8. Who Am I? An Emic Approach to the So-Called 'Personal Texts' in Egyptian 'Funerary Literature' (Willems) -- ‎Index of Egyptian Terms in Transliteration -- ‎General Index.